Screening of faecal coliforms and heavy metals in water from the in-situ commercial water filtration dispensers in Skudai, Johor Bahru - Nurul Fatin Mohd Salleh, 1993-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2016